Modeling fear of failure based on self-criticism, maladaptive schemas and Perceived Competence mediated by competitive anxiety in adolescent students . - Fatemeh Ashrafi Dasht Arjaneh; Yousef Dehghani; Faride Sadat Hoseini (مطالعات روانشناسی تربیتی)
The aim of this study was to modelling fear of failure based on self-criticism, maladaptive schemas and perceived competence mediated by competitive anxiety in high school girls student, conducted by correlational model and SEM. The statistical population included the adolescent girl students of the secondary school in Shiraz city, whose number in the study period was 7420 student. In this study, 361 participate were selected based on Cochran's formula. In order to collect data was used Conroy (2002) Fear of Performance Fear Assessment Questionnaire, Thompson & Zuroff (2004) Self-Critical Level Questionnaire, Young Schema Questionnaire (1998), Harter Competence Perception Questionnaire (1982) and Competitive Anxiety Questionnaire Illinois (1990). Data analysis was performed using AMOS 18 software. The results showed that self-criticism in addition to a direct effect mediated by competitive anxiety has a positive and indirect relationship with fear of failure (B = 0.23). Also, maladaptive schemas, in addition to having a direct effect on competitive anxiety mediation, have a positive and indirect relationship with fear of failure (B = 0.21). Finally, in addition to the direct effect mediated by competitive anxiety, the perception of competence has a negative and indirect relationship with the fear of failure (B = -0.26). According to the findings of this study, it can be concluded that competitive anxiety can increase the positive relationship between self-criticism and maladaptive schemas with fear of student failure and on the other hand reduce the negative relationship between the perception of competence and the fear of failure of students.